GAS LEAK DETECTION SYSTEM MONITORING BASED IoT USING MCU NODES WITH GOOGLE FIREBASE COMMUNICATION - Mohammad Imam Syaiffullah; Sumardi Sadi; Roni Suyono (Jurnal Teknik, 2020)
ABSTRACT Liquefied Petroleum Gas (LPG) leak detection system is a precautionary measure for hazards such as a gas cylinder explosion. There have been many incidents of building explosions because the occupants were negligent in anticipating the gas leak. Therefore, this research has made a gas leak detection system that is integrated with the IoT concept using Google Firebase. This tool aims to anticipate the dangers of gas leaks that occur in a room in a building or house. This tool is wrapped in an acrylic box measuring 10 x 11 x 8 cm. By using NodeMCU ESP8266 as the main control, the gas sensor uses MQ - 2 as input, LED, LCD, and buzzer as output. This tool is also equipped with IoT (Internet of Things) so that the room where this tool is installed when a gas leak occurs can provide notifications remotely using an application on a smartphone. From this tool, test results have been obtained for the ideal distance from the gas regulator to the sensor which is 1 cm away by producing a sensor response time of 0.90 seconds and also getting the response time of the tool in sending notifications to the smartphone application of 1.79 seconds. Keywords: LPG, Firebase, IoT, NodeMCU, Gas Detection